Voting on urban land development - Matthias Wrede (Journal of Regional Science, 2021)
In this paper, we analyze several local referendums on land development and land-use regulation in the City of Erlangen (Germany) between 2011 and 2018. To identify the positive influence of the travel distance on approval for land development, we control for distance to the city center and density, employ a two-way fixed-effect~model, and use spatial instruments. We also analyze the heterogeneity of city dwellers' preferences for the development of residential and commercial areas. In particular, we examine the differences between homeowners and tenants in this regard.
Keywords: 320; business and residential land use; distance decay; homeownership; land development; referendum